Hubungan Antara Kualitas Tidur dengan Gangguan Cemas pada Mahasiswa Selama Masa Pandemi COVID-19 - I Gusti Ngurah Ananda Wira Kusuma; Stevanus Christian Surya; I Putu Hendri Aryadi; Made Indira Dianti Sanjiwani; Putu Gede Sudira (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: The COVID-19 pandemic affects various aspects of everyone's life. One of the impacts of the pandemic is psychological disorders, such as decreased sleep quality and anxiety. Until now, there has been no research to assess the relationship between these two conditions in university students during the pandemic era. Therefore, this study aims to evaluate the relationship between decreased sleep quality and anxiety disorders in Indonesia’s university students during the COVID-19 pandemic.Methods: The cross-sectional study was conducted from September to October 2021 on 376 university students, both domiciled in Bali and outside Bali. Data were collected using a questionnaire consisting of participant demographic data, sleep quality assessment using the Pittsburg Sleep Quality Index (PSQI), and measurement of anxiety levels using the Zung Self-Rating Anxiety Scale (SAS). Bivariate analysis was performed using the Pearson correlation test.Result: 294 of the 376 participants had high PSQI scores (>5) and experienced sleep disturbances. Meanwhile, 44 participants reported experiencing anxiety disorders, with detail of 41 participants having SAS scores in the low category and 3 participants having SAS scores in the moderate category. The relationship between the PSQI and SAS variables showed a correlation coefficient of 0.619 and was statistically significant.Conclusion : Decreased sleep quality is positively correlated with anxiety disorders experienced by university students during the COVID-19 pandemic. The author suggests research with larger parameters and population size to get more accurate results.